The Effectiveness of Project-Based Learning (PJBL) in Islamic Education to Improve the Internalization of Social Care Values Among Students at State Senior High School 1 Banyuasin III - Nurul Qomariyah; Fitri Oviyanti; Nurlaila Nurlaila; Muhammad Sirozi; Yulia Tri Samiha (Journal of Educational Sciences, 2026)
Islamic Religious Education (IRE) plays a strategic role in shaping students’ character, particularly in fostering social care values as part of moral and social behavior. However, IRE practices in schools often emphasize cognitive achievement and provide limited meaningful learning experiences that support value internalization in daily life. This condition contributes to students’ low social awareness. Therefore, innovative learning models that integrate Islamic values with real-life social experiences are needed, such as Project Based Learning (PjBL). This study aimed to examine the effectiveness of PjBL in enhancing the internalization of social care character values in IRE learning at SMA Negeri 1 Banyuasin III. Using a quantitative quasi-experimental method with a nonequivalent control group design, the study involved two twelfth-grade classes as experimental and control groups. Data were collected through questionnaires, observation, and documentation, and analyzed using t-tests. The findings revealed a significant improvement in the experimental group, indicating that PjBL is effective in strengthening students’ social care character values.